Project-Based Learning to Foster Entrepreneurial Spirit in Early Childhood Education - Dedeh Komalasari; Maria Hidayanti (THE PRESTISE, 2025)
Fostering an entrepreneurial spirit from an early age is essential, as Early Childhood Education (ECE) serves as the foundation for lifelong learning and readiness for future challenges. The early years are a critical period in which children develop not only cognitive and social-emotional skills but also the character traits necessary for independence and adaptability in life. Therefore, it is crucial to implement learning approaches that align with the unique characteristics of young children—especially their high levels of exploration, creativity, and imagination. Project-Based Learning (PjBL) emerges as a relevant and effective pedagogical approach to cultivate entrepreneurial values in early learners. By engaging children in hands-on, meaningful projects, this model stimulates curiosity and problem-solving, while also embedding entrepreneurial characteristics such as creativity, innovation, responsibility, independence, social communication, and age-appropriate financial literacy. This study explores how project-based learning contributes to the development of entrepreneurial traits in early childhood. It focuses on how learning processes can bring about character development aligned with children’s developmental stages. The findings reveal that when project-based learning is implemented in a manner consistent with the developmental needs of young children, it can effectively foster core indicators of entrepreneurship. These include children's ability to generate innovative ideas, take initiative, act responsibly, communicate effectively in social settings, and manage simple financial tasks. The support of the surrounding environment—particularly the roles of parents and teachers—is crucial in nurturing entrepreneurial values. Their active involvement in the learning process enhances the effectiveness of project-based learning in instilling an entrepreneurial spirit among young children